Hands-On: Curricular Bridging Concepts from Maker Spaces Re-Turning to Hand-Made and Many Hands Making Together - Lee, Carol Marie (Journal of the Canadian Association for Curriculum Studies, 2020)
Poet, author and activist Maya Angelou once told Oprah Winfrey, "Do the best you can until you know better. Then when you know better, do better" (Winfrey, 2011, 2:08). This is practical advice for anyone, including curriculum developers. Angelou was, of course, speaking of forgiveness, fortitude, perseverance and learning. What is interesting for me as an educator is how Angelou went about teaching Winfrey this lesson. Recognizing the power differential between her and the then young Winfrey, she did not begin their relationship by giving advice. She began it by making Winfrey food—a making gesture signifying Winfrey’s equality with the maker. After their meal, Angelou encouraged further communion by sharing poetry made by Paul Laurence Dunbar. The making of things, physical things as in a meal, and/or artistic things as with poetry, is not featured in most Canadian curriculums. Where it does appear, it is framed as optional or vocational; making is something for those with less cognitive aptitude or for artists with marginal value to community commerce. This orientation in curriculums has perhaps led to the under-valuation of “making” as a strategy for relationship building, for reconciliation and for bridging social power divides. My presentation describes a critical discourse analysis I conducted of this popular Angelou quotation and its historical context. I use it to explore insights related to how divides might be bridged through a curriculum that assigns greater value to “making” (Fairclough et al., 2014; van Dijk, 2001; Wodak, 2011; Wodak & Meyer, 2008; Wodak & Reisigl, 2006).